2022
DOI: 10.3390/jcm11154548
|View full text |Cite
|
Sign up to set email alerts
|

The Modified Longitudinal Capsulotomy by Outside-In Approach in Hip Arthroscopy for Femoroplasty and Acetabular Labrum Repair—A Cohort Study

Abstract: Hip arthroscopy is difficult to perform due to the limited arthroscopic view. To solve this problem, the capsulotomy is an important technique. However, the existing capsulotomy approaches were not perfect in the surgical practice. Thus, this study aimed to propose a modified longitudinal capsulotomy by outside-in approach and demonstrate its feasibility and efficacy in arthroscopic femoroplasty and acetabular labrum repair. A retrospective cohort study was performed and twenty-two postoperative patients who u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Guo et al noticed that the albumin-to-alkaline phosphatase ratio can be used as a prognostic biomarker for measuring clinical outcomes after spinal fusion [3]. Regarding lower limb, Cong et al reported a modified capsulotomy approach to facilitate the arthroscopic femoroplasty and acetabular labrum repair, with the clinical data supporting its popularization [4]. Regarding knee, Zhang et al found that anterior cruciate ligament reconstruction using an insertion preservation technique has a protective effect on cartilage degeneration in long-term follow-up [5].…”
mentioning
confidence: 99%
“…Guo et al noticed that the albumin-to-alkaline phosphatase ratio can be used as a prognostic biomarker for measuring clinical outcomes after spinal fusion [3]. Regarding lower limb, Cong et al reported a modified capsulotomy approach to facilitate the arthroscopic femoroplasty and acetabular labrum repair, with the clinical data supporting its popularization [4]. Regarding knee, Zhang et al found that anterior cruciate ligament reconstruction using an insertion preservation technique has a protective effect on cartilage degeneration in long-term follow-up [5].…”
mentioning
confidence: 99%